Hypothyroidism in utero stimulates pancreatic beta cell proliferation and hyperinsulinaemia in the ovine fetus during late gestation. (13th March 2017) - Harris, Shelley E.; De Blasio, Miles J.; Davis, Melissa A.; Kelly, Amy C.; Davenport, Hailey M.; Wooding, F. B. Peter; Blache, Dominique; Meredith, David; Anderson, Miranda; Fowden, Abigail L.; Limesand, Sean W.; Forhead, Alison J.
Abstract : Key points: Thyroid hormones are important regulators of growth and maturation before birth, although the extent to which their actions are mediated by insulin and the development of pancreatic beta cell mass is unknown. Hypothyroidism in fetal sheep induced by removal of the thyroid gland caused asymmetric organ growth, increased pancreatic beta cell mass and proliferation, and was associated with increased circulating concentrations of insulin and leptin. In isolated fetal sheep islets studied in vitro, thyroid hormones inhibited beta cell proliferation in a dose‐dependent manner, while high concentrations of insulin and leptin stimulated proliferation. The developing pancreatic beta cell is therefore sensitive to thyroid hormone, insulin and leptin before birth, with possible consequences for pancreatic function in fetal and later life. The findings of this study highlight the importance of thyroid hormones during pregnancy for normal development of the fetal pancreas. Abstract: Development of pancreatic beta cell mass before birth is essential for normal growth of the fetus and for long‐term control of carbohydrate metabolism in postnatal life. Thyroid hormones are also important regulators of fetal growth, and the present study tested the hypotheses that thyroid hormones promote beta cell proliferation in the fetal ovine pancreatic islets, and that growth retardation in hypothyroid fetal sheep is associated with reductions in pancreatic beta cell mass and circulating insulin concentration in utero . Organ growth and pancreatic islet cell proliferation and mass were examined in sheep fetuses following removal of the thyroid gland in utero . The effects of triiodothyronine (T3 ), insulin and leptin on beta cell proliferation rates were determined in isolated fetal ovine pancreatic islets in vitro . Hypothyroidism in the sheep fetus resulted in an asymmetric pattern of organ growth, pancreatic beta cell hyperplasia, and elevated plasma insulin and leptin concentrations. In pancreatic islets isolated from intact fetal sheep, beta cell proliferation in vitro was reduced by T3 in a dose‐dependent manner and increased by insulin at high concentrations only. Leptin induced a bimodal response whereby beta cell proliferation was suppressed at the lowest, and increased at the highest, concentrations. Therefore, proliferation of beta cells isolated from the ovine fetal pancreas is sensitive to physiological concentrations of T3, insulin and leptin. Alterations in these hormones may be responsible for the increased beta cell proliferation and mass observed in the hypothyroid sheep fetus and may have consequences for pancreatic function in later life. Key points: Thyroid hormones are important regulators of growth and maturation before birth, although the extent to which their actions are mediated by insulin and the development of pancreatic beta cell mass is unknown. Hypothyroidism in fetal sheep induced by removal of the thyroid gland caused asymmetric organ growth, increased pancreatic beta cell mass and proliferation, and was associated with increased circulating concentrations of insulin and leptin. In isolated fetal sheep islets studied in vitro, thyroid hormones inhibited beta cell proliferation in a dose‐dependent manner, while high concentrations of insulin and leptin stimulated proliferation. The developing pancreatic beta cell is therefore sensitive to thyroid hormone, insulin and leptin before birth, with possible consequences for pancreatic function in fetal and later life. The findings of this study highlight the importance of thyroid hormones during pregnancy for normal development of the fetal pancreas.